2015
DOI: 10.1016/j.jqsrt.2014.11.021
|View full text |Cite
|
Sign up to set email alerts
|

Broadband and highly sensitive comb-assisted cavity ring down spectroscopy of CO near 1.57µm with sub-MHz frequency accuracy

Abstract: International audienc

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
36
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 58 publications
(38 citation statements)
references
References 36 publications
2
36
0
Order By: Relevance
“…A higher frequency accuracy can indeed be achieved using a frequency comb. Very recently, by combining a selfreferenced frequency comb with a CRDS spectrometer, we could derive the positions of the 3-0 absorption lines of 12 C 16 O with an accuracy on the order of 300 kHz ( $ 10 À 5 cm À 1 ) [21]. Interestingly, in the range of the 3-0 band, we could measure transition frequencies of the 4-1 hot band for J values up to 24 with an accuracy of about 1 MHz ( $ 3 Â 10 À 5 cm À 1 ).…”
Section: Line Positionsmentioning
confidence: 99%
“…A higher frequency accuracy can indeed be achieved using a frequency comb. Very recently, by combining a selfreferenced frequency comb with a CRDS spectrometer, we could derive the positions of the 3-0 absorption lines of 12 C 16 O with an accuracy on the order of 300 kHz ( $ 10 À 5 cm À 1 ) [21]. Interestingly, in the range of the 3-0 band, we could measure transition frequencies of the 4-1 hot band for J values up to 24 with an accuracy of about 1 MHz ( $ 3 Â 10 À 5 cm À 1 ).…”
Section: Line Positionsmentioning
confidence: 99%
“…In addition to the techniques just illustrated (see also [81][82][83][84]176]), many more instrumental and probe schemes to access overtones were reported in the literature, leading to some beautiful results. One can highlight LIF and stimulated emission pumping involving an intermediate, excited electronic state, as performed by Field and co-workers [177].…”
Section: Cw-crds Based Overtone Spectramentioning
confidence: 99%
“…In addition to supporting reaction dynamics [65], including isomerization processes [66][67][68][69][70], overtone excitation is recognised as driving some of the atmospheric chemistry [71][72][73] and as controlling bond selected chemistry [74,75]. The investigation of overtones generated the local mode theory [76][77][78], the polyad concept [79,80], and, as already suggested, stimulated the development of detection capabilities [81][82][83][84].…”
Section: Introductionmentioning
confidence: 99%
“…There are several advantages to use the CO molecule. First, the ro-vibrational transitions of CO have been well studied, including very weak hot bands and the lines from minor isotopologues [43,44], which allows to use a truly isolated line for high-precision DBT studies. Second, the carbon monoxide gas sample can be easily purified in laboratory by removing the contaminant gases with a cold trap.…”
Section: Interference Due To "Hidden" Linesmentioning
confidence: 99%
“…(4) The relative accuracy of the center frequency of the C 2 H 2 line is about 1.3 ppb (δν 0 /ν 0 ). For the CO lines at the 1.57 µm which will be used in succeeding studies, the line centers have been determined to subMHz accuracy [44], therefore the induced uncertainty on k B is negligible. (5) Recently Bordé has shown that the transit-time broadening is absent in linear absorption spectroscopy in the case of a uniform and isotropic medium [37].…”
Section: Uncertainty Budgetmentioning
confidence: 99%